Genome-wide analysis of SSR and ILP markers in trees: diversity profiling, alternate distribution, and applications in duplication. Issue 1 (December 2017) - Xia, Xinyao; Luan, Lin; Qin, Guanghua; Yu, Li; Wang, Zhi; Dong, Wan; Song, Yumin; Qiao, Yuling; Zhang, Xian; Sang, Ya; Yang, Long
Abstract Molecular markers are efficient tools for breeding and genetic studies. However, despite their ecological and economic importance, their development and application have long been hampered. In this study, we identified 524, 170 simple sequence repeat (SSR), 267, 636 intron length polymorphism (ILP), and 11, 872 potential intron polymorphism (PIP) markers from 16 tree species based on recently available genome sequences. Larger motifs, including hexamers and heptamers, accounted for most of the seven different types of SSR loci. Within these loci, A/T bases comprised a significantly larger proportion of sequence than G/C. SSR and ILP markers exhibited an alternative distribution pattern. Most SSRs were monomorphic markers, and the proportions of polymorphic markers were positively correlated with genome size. By verifying with all 16 tree species, 54 SSR, 418 ILP, and four PIP universal markers were obtained, and their efficiency was examined by PCR. A combination of five SSR and six ILP markers were used for the phylogenetic analysis of 30 willow samples, revealing a positive correlation between genetic diversity and geographic distance. We also found that SSRs can be used as tools for duplication analysis. Our findings provide important foundations for the development of breeding and genetic studies in tree species.